PENGARUH SUKU BUNGA, PENDAPATAN DAN ARUS KAS TERHADAP STRUKTUR MODAL PADA PT. NILAM WANGI MEDAN PERIODE 2013 - 2017 - REBECCA EVADINE (LP2MTBM MAKARIOZ, 2020)
Company must have purposes to gain profit in order to survive continuity of company for long term. The purpose of companyis to maximized profits to increase growth of company. On the other side, need a correction to know company’sachievements during a certain period, this is useful to take action that will be company do in the future that still in line with thepurpose of company. The purpose of this study was to determine and analyze the effect of interest rate, revenue and cashflow towards capital structure at PT. Nilam Wangi Medan period 2013-2017. This method of research is using multiple linearregression analysis with SPSS software. The result showed that interest rate, revenue and cash flow simultaneously andsignificantly positive effect towards capital structure at PT. Nilam Wangi Medan period 2013-2017. In determinationcoefficient (Adjusted R2) variations in variable interest rate, revenue, cashflow is 14,5% towards capital structure at PT.Nilam Wangi Medan period 2013-2017 and the rest are influenced by other variables that is not explained in this study suchas liability,etc. Interest rate partially negative effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017. revenue partially positive effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017. Cashflow partially positive effect and significant towards capital structure at PT. Nilam Wangi Period 2013-2017.